Recria de bovinos de corte em pastagem de Urochloa ruziziensis semeada com a cultura do milho - Braga, Leandro Carvalho (2022)
The objective was to evaluate the effect of the height of Ruziziensis grass pastures sown with the corn crop on the forage canopy characteristics, the nutritive value of forage, animal performance, and animal behavior. The experimental design was randomized blocks with three treatments (heights of pasture) and three replications. The heights of the pasture were: low (17 cm), medium (21 cm), and high (31 cm). Twenty-seven Aberdeen Angus calves (initial body weight = 223.82 ± 5.9 kg; initial age = 10 ± 1.5 months) were used. The grazing system used was continuous stocking with a variable stocking rate. The experimental period was 87 days, divided into three periods of 29 days. An adaptation period of 15 days was used. The pasture sowing was carried out between the rows of the corn crop through the no-tillage system (09/15/2021). The increase in pasture height increased forage mass and forage supply. The animal load decreased with the increasing height of the pasture. The proportion of leaves and senescent material was not altered by the height of the pasture. The stem proportion was higher in the medium and high heights to the low height of the pasture. Pasture heights did not influence the dry matter, mineral matter, organic matter, crude protein, and acid detergent fiber content of the forage. The neutral detergent fiber content was higher for the medium height than the low height. In vitro digestibility of dry matter decreased with the increase of the height of the pasture. The average daily gain was lower for the lowest grazing height, with no difference between the medium and high heights. Pasture heights did not influence body weight gain per hectare. Grazing time was shorter, and rumination time was larger in pastures managed with greater height. Pasture heights did not affect the other activities' time. Ruziziensis grass pastures with 21 to 31 cm in height in late summer and early autumn allow more significant performance of Aberdeen Angus steers than pastures with less height but no altered animal production per area.